'Black Fire': Conceptualisations of Black Liberation and Engaged Views of African and Black Aesthetics in the United States and South Africa. Issue 4 (2nd September 2020) - Dallywater, Lena
Abstract: The article describes the multiple discursive and actual connections between ideas of a 'Black Aesthetic' in both the South African and the US-American contexts during the mid twentieth century. It is centred on knowledge produced between 1965 and 1985, when the Black Power/Black Arts and Black Consciousness movements gained prominence among urban intellectuals. Specific debates and argumentations that focused on black and African aesthetics and the respective groups of actors involved are depicted. The article follows the development of the discussions to the early 1990s, to conclude on actual similarities and differences and the factors that arguably produce them. Throughout, the study follows an actor-centred approach and ultimately counters the broad narrative of a 'United States–South Africa' connection that is circulating in academic and public spheres and questions more generally the focus on geographical locations to understand Black and African ideologies and their entanglements. By doing this, the article wants to contribute to the question how we can approach engaged or radical views of black and African aesthetics comparatively and the presence of those legacies today.